Expression of the Xylulose 5-Phosphate Phosphoketolase Gene, xpkA, from Lactobacillus pentosus MD363 Is Induced by Sugars That Are Fermented via the Phosphoketolase Pathway and Is Repressed by Glucose Mediated by CcpA and the Mannose Phosphoenolpyruvate Phosphotransferase System - Posthuma, Clara C. (American Society for Microbiology, 2002)
Purification of xylulose 5-phosphate phosphoketolase (XpkA), the central enzyme of the phosphoketolase pathway (PKP) in lactic acid bacteria, and cloning and sequence analysis of the encoding gene, xpkA, from Lactobacillus pentosus MD363 are described. xpkA encodes a 788-amino-acid protein with a calculated mass of 88,705 Da. Expression of xpkA in Escherichia coli led to an increase in XpkA activity, while an xpkA knockout mutant of L. pentosus lost XpkA activity and was not able to grow on energy sources that are fermented via the PKP, indicating that xpkA encodes an enzyme with phosphoketolase activity. A database search revealed that there are high levels of similarity between XpkA and a phosphoketolase from Bifidobacterium lactis and between XpkA and a (putative) protein present in a number of evolutionarily distantly related organisms (up to 54% identical residues). Expression of xpkA in L. pentosus was induced by sugars that are fermented via the PKP and was repressed by glucose mediated by carbon catabolite protein A (CcpA) and by the mannose phosphoenolpyruvate phosphotransferase system. Most of the residues involved in correct binding of the cofactor thiamine pyrophosphate (TPP) that are conserved in transketolase, pyruvate decarboxylase, and pyruvate oxidase were also conserved at a similar position in XpkA, implying that there is a similar TPP-binding fold in XpkA.